With so many battery electric buses in operation, why are fuel cell electric buses more relevant than ever? Artikel - F. Juelsgaard, Kristina; J. Yorke, David (Proceedings from the Annual Transport Conference at Aalborg University, 2023)
The bus industry has been a frontrunner in the adoption of zero emission vehicles and their operation. In 2022, zero-emission buses accounted for approximately 12.7%1 of new bus registrations in the European Union, with the uptake growing year on year. Fuel Cell Electric buses (FCEB) and Battery Electric buses (BEB) are complementary zero-emission technologies, and while both offer advantages for fleet operators, there are significant differences that can impact the choice of vehicle: • BEBs often require changes to bus depot activities to accommodate charging time and infrastructure, which can result in schedule changes and reduced asset utilisation for the operator. To gain – or improve - the range of a BEB, opportunity charging along longer routes may be required, which can impact scheduling of buses further. • With their longer range and fast refuelling time, FCEBs can be a ‘drop in’ replacement for a diesel bus and does not suffer from the infrastructure and range issues that affect the service and depot operation of BEBs. When transitioning to zero-emission buses, it is important for the operator to choose the correct technology for the specific route characteristics to ensure that the core purpose of the bus - to move passengers safely and on time - is completed without compromise.